Impact of Leadership Style, Motivation and Training on Employee Performance - Jumady, Edy; Bungatang, Bungatang (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
Purpose: This study examines the influence of leadership style, motivation, and training on employee performance at the Office of Maritime Affairs and Fisheries of South Sulawesi Province. Research Design and Methodology: This research employs a quantitative descriptive method. The population consists of 204 employees, with a sample of 67 respondents selected using Slovin's formula. Primary data were collected through questionnaires distributed to employees. The analysis techniques used include descriptive statistical analysis, validity and reliability tests, normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, linearity test, and hypothesis testing using multiple linear regression analysis, t-test, and F-test. Findings and Discussion: The results show that leadership style does not significantly influence employee performance, while motivation has a positive but insignificant effect. In contrast, training positively and substantially influences employee performance, which is vital in improving work outcomes. Simultaneously, leadership style, motivation, and training positively and significantly affect employee performance, suggesting that these factors collectively enhance organizational performance. Implications: The findings imply that the Office of Maritime Affairs and Fisheries of South Sulawesi Province should reconsider leadership strategies, enhance employee motivation, and consistently implement relevant training programs to improve employee performance. These efforts will help optimize employee productivity and organizational effectiveness.